Investigation of bankruptcy in shipping industry - offshore and marine industry - Chua, Pei Yun (2018)
The Offshore and Marine (O&M) industry has been plagued by negative market sentiments over the years, owing to the precipitated fall in oil prices and low demand for offshore support vessel services. Coupled with the restraint on oil major’s exploration expenditure and the low daily charter rates, O&M companies are increasingly faced with challenging factors that could influence their decision-making for the survivability of the company. In today’s economic landscape, bankruptcy filings are gradually becoming prevalent in the O&M industry. Undoubtedly, the overall weakening financial performances are malicious to the entire industry and the other players across the supply chain. Unfortunately, there are limited studies that investigate the underlying factors that attribute to bankruptcy in the O&M industry. Hence, through a consolidation of the external and internal factors, this paper provides a comprehensive insight into the dominant factors that steered O&M companies to the brink of bankruptcy. This paper adopts both qualitative and quantitative methods to analyze the dominant factors. This is conducted through surveys to gain an overall industry sentiment using the PESTLE model (Political, Economic, Social, Technological, Legal and Environmental), and 3 pillars financial management model (Financial, Investment and Operational). Thereafter, upon the formulation of relative importance which addressed the potential top factors attributing to the state of insolvency, industry views were collated from interviews of industrial professionals. In parallel, an in-depth investigation on several underperformed O&M companies case studies was undertaken to identify the dominant factors. The dominant factors derived from the findings and analysis are geopolitical conflicts, political instability, current economy, oil prices volatility, cost of development, financial risk, investment in diversified industry and operational risk. Included is a discussion of industry lessons and insights gained from the studies on bankruptcy in O&M industry. Alongside, guidelines were produced as a reference for O&M industry to mitigate potential bankruptcies and achieve its sustainable financial goals. Ultimately, this paper seeks to address the key factors in bankruptcy of O&M companies and provide substantial insights for the organization to minimize potential risk of bankruptcy.